Acute Kidney Injury in Patients Receiving Systemic Treatment for Cancer: A Population-Based Cohort Study. (13th November 2018) - Kitchlu, Abhijat; McArthur, Eric; Amir, Eitan; Booth, Christopher M; Sutradhar, Rinku; Majeed, Habeeb; Nash, Danielle M; Silver, Samuel A; Garg, Amit X; Chan, Christopher T; Kim, S Joseph; Wald, Ron
Abstract: Background: Patients undergoing treatment for cancer are at increased risk of acute kidney injury (AKI). There are few data on AKI incidence and risk factors in the current era of cancer treatment. Methods: We conducted a population-based study of all patients initiating systemic therapy (chemotherapy or targeted agents) for a new cancer diagnosis in Ontario, Canada (2007–2014). The primary outcome was hospitalization with AKI or acute dialysis. We estimated the cumulative incidence of AKI and fitted Fine and Gray models, adjusting for demographics, cancer characteristics, comorbidities, and coprescriptions. We modeled exposure to systemic therapy (the 90-day period following treatments) as a time-varying covariate. We also assessed temporal trends in annual AKI incidence. Results: We identified 163 071 patients initiating systemic therapy of whom 10 880 experienced AKI. The rate of AKI was 27 per 1000 person-years, with overall cumulative incidence of 9.3% (95% CI = 9.1% to 9.6%). Malignancies with the highest 5-year AKI incidence were myeloma (26.0%, 95% CI = 24.4% to 27.7%), bladder (19.0%, 95% CI = 17.6% to 20.5%), and leukemia (15.4%, 95% CI = 14.3% to 16.5%). Advanced cancer stage, chronic kidney disease, and diabetes were associated with increased risk of AKI (adjusted hazard ratios [aHR] = 1.41, 95% CI = 1.28 to 1.54; 1.80, 95% CI = 1.67 to 1.93; and 1.43, 95% CI = 1.37 to 1.50, respectively). In patients aged 66 years or older with universal drug benefits, diuretic, and angiotensin-converting enzyme inhibitor/angiotensin receptor blocker coprescription was associated with higher AKI risk (aHR = 1.20, 95% CI = 1.14 to 1.28; 1.30, 95% CI = 1.23 to 1.38). AKI risk was further accentuated during the 90-day period following systemic therapy (aHR = 2.34, 95% CI = 2.24 to 2.45). The annual incidence of AKI increased from 18 to 52 per 1000 person-years between 2007 and 2014. Conclusion: Cancer-related AKI is common and associated with advanced stage, chronic kidney disease, diabetes, and concomitant receipt of diuretics or angiotensin-converting enzyme inhibitors/angiotensin receptor blockers. Risk is heightened in the 90 days after systemic therapy. Preventive strategies are needed to address the increasing burden of AKI in this population.